Biophysical Regulation of Vascular Differentiation and Assembly (Biological and Medical Physics, Biomedical Engineering,, 2018)
This book updates and expands on various aspects of the vasculature's microenvironment and how these regulate differentiation and assembly. Discussed in this new edition are efforts to capitalize on combining engineering techniques, to study and manipulate various biophysical cues, including: endothelial cell-pericyte interactions (Davis), mechanical forces to regulate vascularization in three-dimensional constructs (Levenberg), how matrix properties and oxygen tension regulate vascular fate and assembly (Gerecht), biophysical cues in relation to vascular aging (Ferreira), 3D printing of complex vascularized tissue (Hibino), the harnessing of biophysical cues for therapeutic vasculature interfacing with the damaged brain (Segura) and finally, the infarcted heart (Grayson). This second edition of Biophysical Regulation of Vascular Differentiation and Assembly provides an interdisciplinary view of vasculature regulation through various biophysical cues and presents recent advances in measuring and controlling such parameters. This book will be of interest to biologists, biophysicists and engineers who work with vascular differentiation and assembly.